Peacekeeping Forces, Jurisdiction and Immunity: A Tribute to George Barton - Clark, Roger S (Victoria University of Wellington Law Review, 2012)
George Barton wrote his PhD thesis at Cambridge on "Jurisdiction over Visiting Forces". He published three spinoffs from the thesis in the British Yearbook of International Law. In all of these – each a tour de force in examining elusive and arcane State practice – he was at great pains to deny various supposed customary rules recognising immunity of foreign armed forces in the courts of a State in which they were visiting by consent. He worked in the United Nations Secretariat in New York just as the practice of United Nations peacekeeping began to develop. In this tribute, I try to imagine that he returned to the subject some 60 years later. Affecting, as best I can, the style of Dr Barton circa 1950, I offer some guesses as to how he might assess six decades of developments in law and practice in the multilateral context in which the United Nations, and especially the Secretariat and the Security Council, have been major actors.